PENGARUH PROGRAM KONSERVASI HUTAN KOTA OLEH (PEMERINTAH DAN SWASTA) DAN KEPEDULIAN MASYARAKAT TERHADAP KONSERVASI HUTAN KOTA (2013) - Nurman Hakim Hidayat (Program Studi Manajemen Lingkungan, 2017)
The objective of this research was to know the effect of the forest conservation program and caring community against effectiveness of urban forest conservation. This research applied true experimental design with posttest-only control design. This populations of this research is part of community around urban city. The samples of this research were community as government program and private program. The instrument of this this research namely Effectiveness test and caring scale questionnaire. The research data are quantitative data consisted by score Effectiveness test and caring scale, collected on February until May 2013. Data were analysed by linear variant statistical analysis (ANAVA), continued with Tukey test. The result of research indicated that there were conservation program toward the effectiveness of urban forest conservation. community with government program having the value of effectiveness higher then from private program. Based on this research, the researcher suggest to the government to keep the program run and countinues and for private / corporation must have another program to make conservation program more effective